(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
This paper presents a study among cadets from the Vasil Levski National Military University of their energy status during complex tactical exercises. Their energy intake and energy expenditure were studied, using the methods of tabular timing and food intake history. The values ​​of the studied quantities were compared with the national physiological norms for nutrition of the population of the Republic of Bulgaria. The energy status of the cadets during complex tactical exercises was determined by comparing the studied energy expenditure and energy intake.